The Analysis of Determinants Affecting Consumers’ Decision to Choose Starbucks - Lusiah, Lusiah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study is to determine the factors that influence the decision to choose Starbucks. The population in this study amounted to 395 respondents. The data analysis technique in this study is multiple linear regression analysis, t-test, F-test, and coefficient of determination. Variables that influence the decision to choose Starbucks are cultural, social, personal and psychological. The result of the partial test and simultaneously stated that the cultural variables, social variables, personal variables, and psychological variables influence the decision to choose Starbucks.